Demograficzne uwarunkowania zmian społecznych i ekonomicznych w regionie Azji i Pacyfiku - Jurek, Łukasz (Demographic Background of Social and Economic Changes in the Region of Asia and Pacific, 2008)
The effect of second demographic transition is systematic growth of old people's share in population. This process is typical for populations in all over the world, but nowadays it is especially intensive in the region of Asia and Pacific. In the future demographic changes will cause there many economic and social problems. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 98-109